The Impact of the Covid-19 Pandemic on Mental Condition and the Need for Psychological Support of Students in Jakarta - Susanto, Susanto (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The Covid-19 pandemic situation has demanded all aspects to adjust. Students are forced to make various adjustments, both learning patterns, demands for adapting new habits, and adherence to health protocols. However, the mental impact on students is not yet known. This study aims to identify the impact of the Covid-19 pandemic on the mental condition of students and the need for psychological support needed for students. This study uses a qualitative method with data collection techniques through online surveys with the target of student respondents coming from Jakarta and the selection of respondents is random and the analysis is carried out descriptively. This study found that the impact of the Covid-19 pandemic on the mental condition of students in Jakarta included; feelings of boredom, confusion, fear, anxiety, and stress. The support needed for students facing the Covid-19 pandemic is family support, friend support, and facility support to carry out positive activities.Situasi pandemi Covid-19 telah menuntut semua aspek untuk menyesuaikan. Peserta didik dituntut melakukan berbagai penyesuaian, baik pola belajar, tuntutan adaptasi kebiasaan baru serta kepatuhan pada protokol kesehatan. Namun demikian, belum diketahui dampak secara mental terhadap peserta didik di Jakarta. Penelitian ini bertujuan untuk mengidentifikasi dampak pandemi covid-19 terhadap kondisi mental peserta didik dan kebutuhan dukungan psikologis yang diperlukan bagi peserta didik.Â Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data melalui survey secara online dengan sasaran responden peserta didik berasal dari Jakarta dan pemilihan responden secara random serta analisis dilakukan secara deskriptif. Penelitian ini menemukan bahwa dampak pandemi covid-19 terhadap kondisi mental peserta didik di Jakarta meliputi; perasaan bosan, bingung, ketakutan, cemas dan stress. Dukungan yang diperlukan bagi peserta didik menghadapi pandemi covid-19 yaitu dukungan keluarga, dukungan teman dan dukungan fasilitas untuk melaksanakan kegiatan positif.Â